CREATION OF DROUGHT-RESISTANT VARIETIES OF SOFT WHEAT FOR RAINFED AREAS OF UZBEKISTAN - Bakhramova Nilufar Nazarovna; Kakhorova Nazokat Poyanovna (Journal Park Publishing, 2022)
In recent years, changes in nature have had a number of negative consequences, especially in the cultivation of crops. Therefore, today it is important to select drought-resistant varieties of crops and introduce them in areas with low water supply. In this work, two-season (two-handle) varieties and lines of wheat are defined as drought-resistant under laboratory conditions. According to the results of studies in 15% sucrose solution, 2 lines were highly resistant, 1 line - moderately resistant and 1 line - moderately weakly resistant relative to the control. Studies of these lines are given.
Keywords: two-season; facultative; varieties